Determinants of Company Value with Company Growth as a Moderating Variable - Putri Jesika Butar-butar; I Dewa Nym Badera (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to obtain empirical evidence regarding the effect of CSR disclosure and capital structure on firm value by using firm growth as a moderating variable. The sample in this study were metal industry companies and the like listed on the IDX for the 2018-2022 period. The research sample was 17 companies with 68 observation data determined by the purposive sampling method. Data were analyzed using Moderated Regression Analysis (MRA). The results of this study indicate that CSR disclosure has a negative effect on firm value, capital structure does not affect firm value, and firm growth cannot moderate the effect of CSR and capital structure on firm value. The implication of this study is to provide benefits for all stakeholders such as internal companies and investors.